STERNO-COSTO-CHONDRO-CORACOIDAN MUSCLE - A CASE REPORT - SRIDHAR.K,; RAJESH.B,; SANGEETHA.K, (International Journal of Pharma and Bio Sciences, 2015)
Pectoralis minimus is a rare muscle usually found in the pectoral region. The aberrant muscle in the present report was arising from the first two costal cartilages and the second chondro-sternal joint of right side. The tendon of the muscle inserted into the superior surface of coracoid process and continued laterally to merge with coracoacromial ligament and coracohumeral ligament. This muscle was unique in its attachment and not reported previously. Pectoralis minimus may help in scapulo humeral rhythm. The knowledge of this aberrant muscle helps radiologist and surgeons in the diagnosis and surgical interventions of the area.